Hollywood : the oral history - Basinger, Jeanine; Wasson, Sam (Harper, an imprint of HarperCollinsPublishers, 2022)
"The real story of Hollywood--as told by such luminaries as Steven Spielberg, Frank Capra, Katharine Hepburn, Alfred Hitchcock, Harold Lloyd, Jordan Peele, and nearly four hundred others--reveals a fresh history of the American movie industry from its beginnings to today"--Dust jacket flap.